Encouraging entrepreneurship and economic growth - David Ahlstrom; Amber Y. Chang; Jessie S. T. Cheung (Journal of Risk and Financial Management, 2019)
The economy has seen unprecedented growth in the past two centuries, raising average incomes by 30-fold. With this added wealth, living standards also improved greatly. Although many factors impact economic growth, it is accepted that entrepreneurship plays a key role. Therefore, understanding the antecedents of entrepreneurship and the link to economic development, often through institutions, should be of higher importance to researchers and policymakers. This Special Issue of the Journal of Risk and Financial Management sought to provide a brief overview of the economic growth literature and its link with entrepreneurship while adding insight through the Special Issue papers regarding the drivers of entrepreneurship in different contexts. Thus, the papers gathered here addressed several aspects of entrepreneurship and how it may be encouraged through networking, cornerstone investors in initial public offerings, new financing methods such as with cryptocurrencies, and through entrepreneur health. The research sites were primarily in Asia. This lead paper summarizes the issue's papers while also providing a short overview of the economic growth literature and its link to entrepreneurship and institutions. This Special Issue, thus contributes to the empirical and theoretic research on the drivers of entrepreneurship and the association with economic growth.
Keywords: 330; Asia; economic growth; entrepreneurial finance; entrepreneurship; institutional theory